Sanksi Tindak Pidana Korupsi oleh Pegawai Negeri dalam Prespektif Fiqih Jinayah - Yuli Rohmatul Hidayah (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2019)
The economic crises that hit Indonesia for a long time were caused by corruption. Corruption itself was the result of the absence of integrated control. Corruption is a crime, it is an abuse of authority. It has been known that the perpetrators are state officials who have "authority", and recognized as Civil Servants. This research aims to determine and analyze the philosophical aim of punishments for perpetrators of corruption by Civil Servants in Islamic law tradition. The results of the study are that: firstly, the corruption in Islamic law can be drawn from the words ghulu>l and rishwah as well as from the verses of the qor'an including QS. al-Baqarah (2) 188, al-Mut}affifi>n (83) 1-2, and al-A'ra>f (7) 33. Secondly, that the sanctions contained in Law No.20 of 2001 Article 8 already felt appropriate and fair, if viewed in terms of the minimum and maximum sentence.